A Turning Point? Recent Developments on Inequality in Latin America and the Caribbean - Leonardo Gasparini; Guillermo Cruces; Leopoldo Tornarolli; Mariana Marchionni (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2009)
This paper documents patterns and recent developments on different dimensions of inequality in Latin America and the Caribbean (LAC). New comparative international evidence confirms that LAC is a region of high inequality, although maybe not the highest in the world. Income inequality has fallen in the 2000s, suggesting a turning point from the significant increases of the 1980s and 1990s. There have been some significant improvements toward the reduction in inequalities in the access to primary and secondary education, and to some services (water, sanitation, electricity, cell phones). However, there is an increasing gap between the rich and the poor in the access to tertiary education, and important differences in the access to new technologies.
Keywords: C15; D31; I21; J23; J31; 330; inequality; distribution; education; Latin America; Caribbean; Einkommensverteilung; Haushaltseinkommen; Bildungsniveau; Lateinamerika; Karibische Staaten